SURVEY KETERAMPILAN PASSING BAWAH BOLA VOLLY DI EKSTRAKURIKULER SMPN 6 MUARA UYA - Muhamad Adi Pratama; Perdinanto; Akhmad Amirudin (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
Underpassing is a basic skill that must be mastered in order to be able to play volleyball by receiving the ball from the serve and then passing to a teammate to attack. This research aims to determine the skills in passing under volleyball of extracurricular students at SMPN 6 Muara Uya. The method used is quantitative descriptive. The population used in this research was extracurricular volleyball students at SMPN 6 Muara Uya, totaling 15 male students. Basically, total sampling technique was used for this research. This research uses data collection techniques using a Volleyball Skill Test Passing test. The results of the data obtained from research on the level of volleyball underpassing skills of extracurricular students at SMPN 6 Muara Uya are generally in the "Very Less" category, there are 8 students in the very poor category with a percentage of 53.3%, 6 students in the poor category with a percentage of 40.0%, 1 students in the medium category with a percentage of 6.7%, 0 students in the good category with a percentage of 0%, and 0 students in the very good category with a percentage of 0%. Efforts are needed to improve the volleyball underpassing skills of extracurricular students at SMPN 6 Muara Uya. These efforts can be made through more focused and intensive training, as well as by providing better guidance and direction from the supervising teacher.